2020
DOI: 10.3390/plants9040483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Essential Nutrients on Roots Growth and Lifespan of Huanglongbing Affected Citrus Trees

Abstract: Understanding citrus tree root development and dynamics are critical in determining crop best nutrient management practices. The role of calcium (Ca) and magnesium (Mg), manganese (Mn), Zinc (Zn), and boron (B) on huanglongbing (HLB) affected citrus trees' root growth and lifespan in Florida is not fully documented. Thus, the objective of this study was to determine the impact of foliar and ground-applied essential nutrients on seasonal fine root length density (FRLD; diameter (d) < 2 mm) and coarse roots (d >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 43 publications
(83 reference statements)
4
50
0
Order By: Relevance
“…Trees were fertigated with a micro-sprinkler Max−14 (Maxijet Inc., Dundee, FL, USA), Fill-in blue emitters were placed 15 cm from the tree trunk. The irrigation was assisted with a 172.4 kpa irrigation pump at a flow rate of 45 L h −1 [ 30 ]. Citrus SmartIrrigation app, which is available on iOS and Android interfaces, was used to determine daily irrigation duration to meet tree water requirement based on reference evapotranspiration (ET o ) calculated with Penman-Monteith and crop coefficient related to the meteorological data of the study site [ 12 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trees were fertigated with a micro-sprinkler Max−14 (Maxijet Inc., Dundee, FL, USA), Fill-in blue emitters were placed 15 cm from the tree trunk. The irrigation was assisted with a 172.4 kpa irrigation pump at a flow rate of 45 L h −1 [ 30 ]. Citrus SmartIrrigation app, which is available on iOS and Android interfaces, was used to determine daily irrigation duration to meet tree water requirement based on reference evapotranspiration (ET o ) calculated with Penman-Monteith and crop coefficient related to the meteorological data of the study site [ 12 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some essential nutrients (e.g., Ca, Mg, Fe, Mn, Zn, and B) are less available for uptake by some crops under alkaline soil conditions [ 28 , 29 ]. Therefore, multiple annual fertilizer applications in association with scheduling fertigation, and products with incorporated elemental sulfur (S) that releases S to lower soil pH were utilized to enhance nutrient availability and minimize the nutrient leaching probability [ 28 , 30 ]. Manganese (Mn) deficiency is normally a worldwide problem predominantly manifested in the spring after a cold winter [ 2 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the disease is widespread, citrus trees may live for only 5–8 yr and never produce usable fruit (Alvarez et al., 2016; Roistacher, 1996). More importantly, research done over the past 20 yr has shown that citrus fibrous roots are mostly within the 0‐ to 30‐cm soil depth (Atta, Morgan, Hamido, & Kadyampakeni, 2020; Kadyampakeni, Morgan, Schumann, & Nkedi‐Kizza, 2014; Morgan, Obreza, & Scholberg, 2007) and can be restored with modified micronutrient application rates.…”
Section: Introductionmentioning
confidence: 99%
“…Research that demonstrated that citrus greening symptoms could be reduced by foliar applications of micronutrients, especially Mn, Zn, B, and Mg, and other physiologically active compounds, such as salicylic acid and phosphite (Pustika et al, 2008;Shen et al, 2013;Stansly et al, 2014). Combined soil and/ or foliar application of the above nutrients to stimulate FRLD and improve root lifespan on citrus greening affected Sweet oranges with emphasis on root-zone soil pH (Atta et al, 2020 (Boina et al, 2010;Tiwari et al, 2012) while few studies evaluated their efficacy in the field (Qureshi and Stanslay, 2007;Abbaszadeh et al, 2011;Rao and Shivankar, 2011). Three IGRs, pyriproxyfen (juvenile hormone mimic), buprofezin and diflubenzuron (both are chitin synthesis inhibitors), showed promising ovicidal and nymphicidal activities against ACP, as well as adverse effects on reproduction (both fecundity and egg viability) and morphology of adults emerging from treated older nymphs (Boina et al, 2010;Tiwari et al, 2012).…”
Section: Effect Of Different Treatments On the Citrus Greening Incidence (% Citrus Greening Infected Plant) And Severitymentioning
confidence: 99%